2018
DOI: 10.12972/kjhst.20180034
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Lettuce Growth Characteristics Under Different LED Light Intensities in a Closed-type Plant Factory

Byeong Hyo Cho,
Tae Hwan Kang,
Chung Su Han
et al.

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…1A). However, a significant and progressive increase was observed over time, reaching a maximum of 1,753 cm 2 with 150 kg ha -1 N + 6 kg ha -1 Mg at 60 dat, and the treatments in general had a significant average value of 1,533 cm 2 , which is higher than the 902.3 cm 2 reported by Cho et al (2018) in 'Cheongchima' lettuce subjected to a light intensity of 200 μmol m -2 s -1 . It should be noted that one of the main functions of leaves is the interception of solar radiation to carry out the photosynthesis process, where a greater LA allows a greater absorption of radiation and thus achieve maximum physiological development (Frąszczak and Kula-Maximenko, 2021).…”
Section: Leaf Area (La) and Leaf Area Ratio (Lar)mentioning
confidence: 57%
See 1 more Smart Citation
“…1A). However, a significant and progressive increase was observed over time, reaching a maximum of 1,753 cm 2 with 150 kg ha -1 N + 6 kg ha -1 Mg at 60 dat, and the treatments in general had a significant average value of 1,533 cm 2 , which is higher than the 902.3 cm 2 reported by Cho et al (2018) in 'Cheongchima' lettuce subjected to a light intensity of 200 μmol m -2 s -1 . It should be noted that one of the main functions of leaves is the interception of solar radiation to carry out the photosynthesis process, where a greater LA allows a greater absorption of radiation and thus achieve maximum physiological development (Frąszczak and Kula-Maximenko, 2021).…”
Section: Leaf Area (La) and Leaf Area Ratio (Lar)mentioning
confidence: 57%
“…In this regard, Liu et al (2014) stated that the application of 200 kg ha -1 N (0.39 g/plant) in lettuce saw a higher value than the dose of 400 kg ha -1 N (0.12 to 0.31 g/plant) and the control (0.14 g/ plant) in terms of accumulated dry biomass at 50 dat. Similarly, Cho et al (2018) reported that the dry mass at 20 dat reached values of 3.03 g/plant under light intensities of 200 μmol m -2 s -1 .…”
Section: Dry Biomassmentioning
confidence: 81%
“…The reflectance spectrum of 648-683 nm increased during the maturity process of the oriental melons, while the reflectance spectrum of 770-818 nm decreased. It is known that a reflectance spectrum of approximately 670 and 800 nm is related to the chlorophyll absorption of crops [44,45]. Thus, these changes are considered to be due to the progressive change in the color of the oriental melons from green to yellow.…”
Section: Hyperspectral Data and Vipmentioning
confidence: 99%
“…Lettuce (Lactuca sativa L.) is an important leafy vegetable because of its high production and consumption in Korea [1]. It is one of the most suitable crops for closed-type plant factory research [2], and growing lettuce in controlled closed environments is gaining popularity because it offers up to 100 times higher annual productivity than field growing [3].…”
Section: Introductionmentioning
confidence: 99%